Multiple intelligences instrument development: Identification system of multiple intelligences tutor - Mery Berlian; Iqbal Miftakhul Mujtahid; Rian Vebrianto; Musa Thahir (REID (Research and Evaluation in Education), 2020)
Research instruments are an important factor in a study in which the truth of researched results lies that determines the conclusion. Instruments are used to collect data and measure a research variable's object. This study aimed to retest a valid, consistent, and reliable instrument related to multiple intelligences previously developed by McClellan Conti. In this study, Multiple intelligences adapted from American psychologist, Howard Gardner, consisted of nine constructs, namely: (1) physical/kinesthetic, (2) existential/spiritual, (3) interpersonal, (4) intrapersonal, (5) logical thinking, (6) musical/rhythmic, (7) naturalistic, (8) verbal, and (9) visual. Designed as a survey study, it involved 140 respondents from primary education tutors of Universitas Terbuka at Pekanbaru selected using simple random sampling techniques. The data was analyzed using SPSS version 23.00 for Windows. The results showed that all questionnaire items were valid and reliable with a high average Cronbach Alpha reliability value (0.763 0.6), and every statement item has a high value (0.786 – 0.887) with a total construct value of 0.859.  This study provides an alternative assessment related to multiple intelligence. Knowing each tutor's multiple intelligences will make the tutor focus more on the superiority of his intelligence. This will have good consequences for the development of the student learning process.